2018
DOI: 10.1371/journal.pone.0194474
|View full text |Cite
|
Sign up to set email alerts
|

Of cattle and feasts: Multi-isotope investigation of animal husbandry and communal feasting at Neolithic Makriyalos, northern Greece

Abstract: The aim of this study is to investigate livestock husbandry and its relationship to the mobilization of domestic animals for slaughter at large communal feasting events, in Late Neolithic Makriyalos, northern Greece. A multi-isotope approach is built that integrates analysis of: δ13C and δ15N values of human and animal bone collagen for understanding long-term dietary behavior,Incremental δ13C and δ18O values of domestic animal tooth enamel carbonate for assessing seasonal patterns in grazing habits and mobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 78 publications
3
23
0
1
Order By: Relevance
“…and mammalian body tissue (Vaiglova et al, 2018;Wang, Tang, & Dong, 2018;Whelton et al, 2018). These factors are case-specific and altered by environmental proxies like topography, weathering rates, climate, and anthropogenic disturbance (Bentley, 2006).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…and mammalian body tissue (Vaiglova et al, 2018;Wang, Tang, & Dong, 2018;Whelton et al, 2018). These factors are case-specific and altered by environmental proxies like topography, weathering rates, climate, and anthropogenic disturbance (Bentley, 2006).…”
supporting
confidence: 89%
“…Commonly, Sr isotope ratio distribution studies rely on a suite of different sample types, with little focus on how reliably geological Sr output is transferred through vegetation, hydrology, and mammalian body tissue (Vaiglova et al, ; Wang, Tang, & Dong, ; Whelton et al, ). These factors are case‐specific and altered by environmental proxies like topography, weathering rates, climate, and anthropogenic disturbance (Bentley, ).…”
Section: Introductionmentioning
confidence: 99%
“…Other possible plants that may have been consumed by the C . elaphus in question are sedges and forbes or grasses (including weeds such as Cynodon dactylon ) [ 45 ] with C 4 photosynthetic pathway, neither of which have been attested for prehistoric wild mammals on the northern side of the Mediterranean basin. Similarly, high δ 13 C values have been recorded in modern C .…”
Section: Resultsmentioning
confidence: 99%
“…elaphus was common in Sicily during the early Holocene, it is not clear why these animals should have been introduced. To date the only prehistoric ungulates from southern European contexts that have been found to have δ 13 C values as high as the three deer specimens from Fontana Nuova are domestic cattle specimens from the Late Neolithic site of Makriyalos in northern Greece [ 45 ]. Recent analyses on Bos taurus from this site have shown that some individuals acquired large proportions of their feed from pastures rich in C 4 vegetation that may have included weeds such as Cynodon dactylon or, more likely, plants in marshy coastal environments enriched in 13 C. In the case of the cattle from Makriyalos, their feeding areas were influenced by human management, whilst it is not clear why, if the 13 C-enriched C .…”
Section: Discussionmentioning
confidence: 99%
“…In the current case, the collagen values obtained from a bovine rib of Structure VI of Arruzafa (δ 15 N = +5.14 and δ 13 C = −22.56) line up with those of pasturing animals nourished by C3 plants(Vaiglova et al, 2018). The adult humans of the study, in turn, display approximate δ 15 N values of 4.46‰ with respect to bovine individual, showing a higher position in the trophic chain.…”
mentioning
confidence: 99%